2003
DOI: 10.1038/sj.sc.3101456
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric spinal cord injury in Sweden; how to identify a cohort of rare events

Abstract: Study design: Register study enhanced and verified by medical records and personal interviews and examinations. Settings: Sweden. Objectives: To define a method of identifying a study population of rare events. To point out the relative importance of every step, an example is given of identifying persons who sustained traumatic spinal cord injury (SCI) in childhood. Methods: Cases were identified in seven steps that all needed to be fulfilled, from definition of selection criteria through combination of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…2 Dislocation of other and unspecified parts of neck S13. 4 Sprain and strain of cervical spine S14.0 Concussion and edema of cervical spinal cord S14. 1 Other and unspecified injuries of cervical spinal cord S22.0…”
Section: Appendixmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Dislocation of other and unspecified parts of neck S13. 4 Sprain and strain of cervical spine S14.0 Concussion and edema of cervical spinal cord S14. 1 Other and unspecified injuries of cervical spinal cord S22.0…”
Section: Appendixmentioning
confidence: 99%
“…Only a few population-based estimates of paediatric TSCI exist. 3,4 The incidence of spinal cord injuries was 1.9 per million among children aged 0-18 years in Finland in the period 1997-2006. 3 A study from Sweden found an incidence of 4.6 per million children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 A common problem for many administrative database researchers is whether the diagnosis code in question detects all true cases in these databases, for example. 5 Blomqvist 4 discusses three methodological approaches for assessing the completeness of registration of cases. The first is to compare the data source with several other independent data sources, the second is review of medical records and the third builds on a comparison between total number of cases in different sources.…”
Section: Introductionmentioning
confidence: 99%